2022
DOI: 10.1088/1742-6596/2232/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

A smoking behavior detection method based on the YOLOv5 network

Abstract: Smoking in public places not only brings about some safety hazards, but also does harm to people’s lives, property and living environment. A smoking behavior detection model based on deep learning is trained for the concern of environment and safety. First, a vertical rotation data enhancement method is adopted in the preprocessing stage to extend the dataset and increase the objects of detection. Then, the channel attention module is introduced in backbone network to calibrate the feature response. Finally, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, the Large Kernel Attention (LKA) mechanism enables adaptability in both spatial and channel dimensions, enhancing the perceptual field capture and remote dependence 12 . Studies also shown that fusing YOLOv4 with CBAM 13,14 , as well as integrating SE-Net into YOLOv5 15 , significantly improved detection accuracy and recall. These studies demonstrate that feature enhancement based on attention mechanisms can effectively improve feature map representation and detection performance.…”
Section: Related Workmentioning
confidence: 93%
“…Furthermore, the Large Kernel Attention (LKA) mechanism enables adaptability in both spatial and channel dimensions, enhancing the perceptual field capture and remote dependence 12 . Studies also shown that fusing YOLOv4 with CBAM 13,14 , as well as integrating SE-Net into YOLOv5 15 , significantly improved detection accuracy and recall. These studies demonstrate that feature enhancement based on attention mechanisms can effectively improve feature map representation and detection performance.…”
Section: Related Workmentioning
confidence: 93%
“…To further validate the performance of the method in this paper, a comparison test is set up to compare the algorithm in this paper with the mainstream algorithms in the field of target detection under the same experimental environment. Faster R-CNN, a representative of two-stage target detection algorithms, and SSD, YOLOv3 [15] , YOLOv4-tiny [16] , and YOLOv5, representatives of one-stage target detection algorithms, were selected. The experimental results are shown in Table 6.…”
Section: Ablation Experimentsmentioning
confidence: 99%
“…They set the training set (validation set + training set) and the test set of the FER dataset at 80.0% and 20.0%, respectively [8]. Xiangkui Jiang et al proposed a smoking behavior detection method based on YOLOv5 [9], using a homemade smoking behavior dataset for training and setting the proportion of training set to test set to 7:3. Fei Yang et al proposed a street image external air conditioner unit detection method [10], setting the homemade air conditioner external unit dataset in the proportion of training set (validation set + training set) and test set as 7.4:2.6.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, datasets have a very important role in tasks, such as object detection, and they can affect the accuracy of the analysis results, but there is no uniform method for dividing the proportion of datasets. Sangwon Kim et al [8,[10][11][12] divided the dataset into a training set, as well as a test set; Jia Yao et al [9,13,14,18] divided the dataset into a training set, validation set, and test set. Kai Huang et al [13,14,18] used dataset partitioning proportions recommended by neural network authors, and Sangwon Kim et al [7][8][9][10][11][12]18] did not specify the method of dataset grouping proportions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation